Sistema de inferencia difusa basado en relaciones Booleanas - Espitia Cuchango, Helbert Eduardo; Soriano Méndez, José Jairo (Ingeniería, 2010)
This paper describes a fuzzy-inference system that is based on Boolean relations. Boolean logic is recognized as a useful tool for automata and digital systems design. An alternative to improve automata systems consists in smoothing the crisp sets into fuzzy sets. The purpose to perform a continuous action on the actuator; by making this change, a new fuzzy inference system based on Boolean relations arises. Although the original proposal was formulated so as to consider automata systems, it is clear that this approach can be extended to more general fuzzy inference systems.